APPLICATIONAL OF THE C4.5 ALGORITHM INDETERMINING AIR QUALIT - Fandi Rahmadsyah Panggabean; Eko Hariyanto; Sri Wahyuni (Sean Institute, 2022)
The C4.5 algorithm produces an accuracy rate of 63.37% with the resulting attributes with a total of 13 attributes and 9357 data in classifying. The results of the model carried out are quite good by looking at the accuracy value generated because the data can be recognized by data that has no class, even though it is not 100% perfect. The author hopes that further research will apply the same parameters to avoid missing values in pre-processing data. It is hoped that further research will be developed by applying this classification model with other and larger data.